Increasing the Benefits of Renovation: Exploring the potential of increased floor area for financial and environmental benefits in existing multi-family residential buildings - Ghafoori, Seidpooyan; Javadian, Farzad (My University, 2024)
Property owners are under significant pressure to carry out energy-efficient renovations due to the urgent requirement to meet EU climate goals. Nevertheless, substantial initial investment outlays and a perceived absence of immediate advantages frequently result in the delay of such renovations. This study investigates the potential financial and environmental advantages of expanding the floor(s) when renovating multi-family residential buildings in Sweden. The study employs a comprehensive approach that combines Life Cycle Cost (LCC) and Life Cycle Assessment (LCA) methodologies to assess different renovation strategies across multiple lifespans (10, 15, 20, 35, and 50 years). The research centres around two specific case studies: Blåsutgatan 8 and Byalagsgatan 8, both located in Gothenburg. The main goals are to evaluate the current state of the building, develop renovation scenarios, simulate and optimise energy efficiency, and conduct thorough economic and environmental assessments. The renovation measures under consideration encompass enhancements to walls and roofs, replacement of windows, improved ventilation systems, and installation of photovoltaic panels. The viability of incorporating additional level(s) into an existing building is also examined as a tactic to augment property value and diminish environmental impact. The findings suggest that incorporating extra floors into renovation projects can effectively decrease energy demand, increase property worth, and minimise carbon emissions, thus aligning with the sustainability objectives of the European Union. The best renovation scenario entails implementing both energy-saving measures and vertical expansion, which can yield significant financial gains and environmental advantages. The thesis emphasises the significance of integrating financial and environmental factors into the decision-making processes for renovations. Additionally, it highlights the necessity of implementing supportive policy measures and providing financial incentives to encourage prompt and sustainable renovations. The research offers valuable insights for property owners, housing companies, and policymakers, thereby contributing to the overarching objectives of enhancing energy efficiency and sustainability in the Swedish residential sector.
Keywords: Energy-efficient Renovation Strategies, Life Cycle Cost (LCC), Life Cycle Assessment (LCA), Vertical Expansion, Multi-family Buildings